Paradoksy ruchu Zenona z Elei a labirynt kontinuum: „Achilles i żółw”, „Strzała”, „Stadion” - Placek, Tomasz (Filozofia Nauki, 1997)
In the article three Zeno's paradoxes are reconstructed. They are: „Achilles and the turtle”, „Arrow” and „Stadium”. Together with the paradox of „Dichotomy” (which was analysed by the author elsewhere) they form the question about the nature of continuum. In the paper the following hypothesis is accepted: „Dichotomy” is principally connected with the mathematical theory of continuum, whereas other paradoxes concern the application of this theory to the description of physical motion.